Development of extended theory of planned behaviour factorial model for organic food consumption among Malaysian adults - Jaafar, Nur Aqilah Amalina (2023)
The increasing demand for food has led to modernization and reliance on artificial inputs in agriculture, which has raised people's concerns regarding food safety and the environment. As a result, organic food, which is grown sustainably without synthetic pesticides, fertilizers, and GMOs, is becoming a popular choice for consumers. However, organic food actual consumption remains low in Malaysia, and previous research have mainly focused on predicting people's intention to consume organic food. This study aimed to understand factors influencing intention and actual consumption of organic food among Malaysian adults with two study phases. Phase 1 (quantitative) comprised a pilot survey (stage 1) to test construct validity and reliability of the instrument. This was followed by an actual survey (stage 2) that collected 424 responses to develop an extended theory of planned behaviour (E-TPB) factorial model for organic food consumption among Malaysian adults. Both surveys utilized online sampling through Facebook. The E-TPB model predicted 72.2% of organic food consumption intention, with attitude formed by food safety, health and environmental concerns being the strongest predictor, followed by perceived behavioural control and subjective norm. Gender was found to have a small effect on consumption intention, with women having a higher intention than men. The model predicted 24.2% of actual consumption, with consumption intention being the strongest predictor. The actual consumption was also contributed by food choice motives specifically "food safety and nutrition" and "health and mood" as well as individual monthly income level. Moreover, the study found that trust in organic food certification, labelling, and control moderated the relationship between intention and actual consumption of organic food. In Phase 2, three focus group discussions were conducted via Zoom to explain the factors of organic food consumption identified in the quantitative study. Two discussions were held with regular and non-to-occasional organic food consumers, while the third involved relevant stakeholders. Five themes emerged for organic food perception: "food safety", "accessibility", "affordability", "production", and "appearance". The factors that influence organic food consumption were categorized as "internal" and "external" factors. The identification of these themes provided specific insights into the psychological and physical factors that affect organic food consumption, thereby enhancing the quantitative findings. The discussions also revealed three primary themes related to organic food certification, labelling, and control: "public confidence", "governance", and "strategy". These themes emphasized the crucial role of trust in strengthening the relationship between intention and actual consumption of organic food by providing key elements associated with it. The quantitative study found that the E-TPB factorial model of organic food consumption had satisfactory predictive validity and fit indices and also established the moderating role of trust in the intention-actual consumption relationship. The qualitative findings further shed light on how identified factors contribute to organic food consumption. The study's results can benefit industry players and stakeholders promoting sustainable development goals through organic food consumption, although caution is advised when generalizing to all Malaysian adults due to the online sampling. Future research could further investigate predictors and variables that mediate or moderate to better understand actual organic food consumption.